Transaksi Game Slot Berupa Chip ditinjau Atas Dimensi Fiqh dan Hukum Islam - Saputra, Andrian; Sandi, Sandi Andika (Fakultas Syariah IAIN Kediri, 2023)
This article examines the practice of buying and selling slot games where chips are included in the gambling buying and selling transactions. This practice is called Maysir in Islamic economics. This kind of buying and selling occurs considering that the level of public interest, from young people to adults, they switch activities by playing this kind of game. Even though a fatwa has been issued from the MUI regarding such games being haram. However, people in Bengkalis consider this game to be just a normal game. The purpose of this research is to find out about forms of buying and selling that are haram carried out with the status of online games. The research carried out is classified as field study type research. Where it uses primary and secondary data sources. The analysis used in this research is to present qualitative analysis to describe and describe slot game transactions in Bengkalis Regency which are studied based on Islamic jurisprudence and law. The current practice of Game Chip trading transactions can be Web-based, starting from advertising on internet-based virtual entertainment, be it Facebook, Instagram, WA and other virtual applications. Thus, the practice of buying and selling slot games is that the object/goods traded contain a maysir component. According to the terms and conditions, buying and selling chips in online games violates Islamic law in buying and selling because it contains elements of gambling (maysir).